2021
DOI: 10.33369/joall.v6i1.13642
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Change Processes of English and Indonesian

Abstract: Phonological change is a language phenomenon that occurs because language users change the distribution of phonemes in a language. The aims of this study are to explain the phonological processes that occur in English and Indonesian and to explain the differences in phonological forms between English and Indonesian. The method used in this study is a contrasting-descriptive method by comparing two languages, namely English and Indonesian. The data were taken from the speech of students taking Indonesian and En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…On the contrary, there is also deletion of sound for Kudus dialect, such as in age (gage in Pati dialect) means "hurry up". (Diani & Azwandi, 2021) states that there are five types of phonological process occur in English and Indonesian, namely assimilation, metathesis, epenthesis, epithesis, and deletion. They observe that epenthesis happens in Indonesian and English learner by inserting sound a sound in a word.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, there is also deletion of sound for Kudus dialect, such as in age (gage in Pati dialect) means "hurry up". (Diani & Azwandi, 2021) states that there are five types of phonological process occur in English and Indonesian, namely assimilation, metathesis, epenthesis, epithesis, and deletion. They observe that epenthesis happens in Indonesian and English learner by inserting sound a sound in a word.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings, the discussion about the vowels, consonants, and Diphtongs found on the Toboali dialect can be made. There is a process of phonological change in every language and this is the reason why Toboali dialect undergoes the change in phonology (Diani & Azwandi, 2021). The phonological change occurs when a speaker pronounces a word in a certain language by changing, adding, inserting, and a sound at the beginning, middle, and end of a word.…”
Section: Discussionmentioning
confidence: 99%
“…In phonology, a set of sounds that are considered equal and can distinguish meaning in a language system is called a phoneme (Diani & Azwandi, 2021). This small set of speech sounds is abstracted by the speakers of a particular language.…”
Section: Introductionmentioning
confidence: 99%
“…They typically solve the pronunciation issue by replacing the nonexistent English sounds with ones in the Indonesian phonological system that are similar enough. They also probably produce reduced pronunciation (Wanrooij & Raijmakers, 2021) Since many non-native speakers and learners of English often face difficulties in producing English fricatives, the production of English fricative sounds by non-native English speakers has received scant attention from many scholars in the field study (Jehma & Phoocharoensil, 2014;Rahman & Idris Asmaradhani, 2020;Sulistyorini & Wibowo, 2021;Wanrooij & Raijmakers, 2021;Weda & Sakti, 2017;Diani & Azwandi, 2021;Utami et al, 2017) Regarding to English fricative consonant pronunciations. it was found that the majority of the participants, who are Indonesian, failed in accurately producing /ʃ/ and /ʒ/ and they often substitute /s/, /z/, or /ʃ/ for both sounds (Weda & Sakti, 2017).…”
Section: Introductionmentioning
confidence: 99%